Analysis of parallelogram mechanism used to preserve remote center of motion for surgical telemanipulator - Trochimczuk, Roman (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an analysis of a parallelogram mechanism commonly used to provide a kinematic remote center of motion in surgical telemanipulators. Selected types of parallel manipulator designs, encountered in commercial and laboratory-made designs described in the medical robotics literature, will serve as the research material. Among other things, computer simulations in the ANSYS 13.0 CAD/CAE software environment, employing the finite element method, will be used. The kinematics of the solution of manipulator with the parallelogram mechanism will be determined in order to provide a more complete description. These results will form the basis for the decision regarding the possibility of applying a parallelogram mechanism in an original prototype of a telemanipulator arm.
Keywords: parallelogram mechanism; surgical telemanipulator; robot minimally invasive surgery; stiffness FEM analysis; RCM mechanism